HPV vaccine program for cervical cancer prevention: how to increase community acceptance? - Purwito, Dedy (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Cervical cancer is Indonesia's second leading cause of death and a significant health financing burden. In 2021, there were 36,633 cases, most caused by HPV (95%). This cancer can be prevented with HPV immunization. The Indonesian government is committed to vaccine-preventing diseases and strengthening health services, focusing on prevention. Immunizations are given to girls in grades 5 and 6 of elementary school to achieve a minimum of 90% immunization coverage and reduce cervical cancer. Support from all parties is needed for the success of this program.